2016
DOI: 10.1002/elan.201600462
|View full text |Cite
|
Sign up to set email alerts
|

2D Hexagonal Boron Nitride (2D‐hBN) Explored as a Potential Electrocatalyst for the Oxygen Reduction Reaction

Abstract: [a] 1IntroductionAs the availability of naturale nergy resources depletes,i t has become increasingly important to finda lternative means of energyp roduction [1].T he most common alternativest of ossil fuels are renewable sources such as hydroelectric power and wind turbines,a nd for transportation purposes,e lectrolysers for fuel cells.T he latteri sa n electrochemical device that relies on the oxidation of af uel, such as methanol, at aw orking electrode (anode), while the protons liberated act as ar edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…17 The observed benecial response at pristine 2D-hBN modied SPEs was attributed to the interaction between 2D-hBN and the roughness of the underlying SPE, whereas the comparatively smooth surface of a GC electrode hindered this. 17 Another key are within the energy sector is improving the overall power of energy storage devices. A fundamental high power solution is to utilise advanced electrode materials within supercapacitor devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 The observed benecial response at pristine 2D-hBN modied SPEs was attributed to the interaction between 2D-hBN and the roughness of the underlying SPE, whereas the comparatively smooth surface of a GC electrode hindered this. 17 Another key are within the energy sector is improving the overall power of energy storage devices. A fundamental high power solution is to utilise advanced electrode materials within supercapacitor devices.…”
Section: Introductionmentioning
confidence: 99%
“…6 We have previously reported that surfactant-free (pristine) 2D-hBN nanosheets exhibit an electrocatalytic behaviour towards the ORR when immobilised upon SPEs. 17 Pristine 2D-hBN reduced the potential required for the ORR to occur by ca. 0.28 V in comparison to unmodied/ underlying SPEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important was to assess the shape and thickness of h-BN flakes before and after the exfoliation process. The commercial h-BN flakes were very thick (~300 nm) [ 27 , 28 ], which corresponded to 900 layers in the individual flake. A large number of flakes was aggregated and connected to each other.…”
Section: Resultsmentioning
confidence: 99%
“…† Analysis of the EDX map shows uniform distribution of B and N atoms with a ratio (1 : 1) of 20.12 at% and 18.81 at% B : N respectively and this composition correlates with expected values for surfactant exfoliated 2D-hBN. 28…”
Section: Physicochemical Characterisationmentioning
confidence: 99%